ISLAMIC BOARDING SCHOOL-BASED ECONOMIC DEVELOPMENT MODEL - Ega Rusanti; Nur Halisa Husain; Ainan Radiyah; Aditya Novri Herlambang (Universitas Islam Negeri Mataram, 2020)
Islamic boarding schools are educational institutions that develop in the archipelago. The function of the pesantren no longer races on the function of the transmission of the religious science and reproduction of ulama, but also as the center of economic development in achieving financial independence. The study uses descriptive qualitative research methods with data collection techniques through interviews and literature studies. The results of the research found that the Islamic Boarding School of Darul Aman Gombara Makassar conducted economic efforts such as laundry, hydroponic, waste processing, canteens, and collaborative business with Central Bank Of Indonesia (BI) in the production of nuggets. The purpose of the business is to build the independence of Islamic boarding schools and the provision of free religious education services for students. But various obstacles are experienced including marketing management and professional human resources in managing the business. It’s needed a strategy in developing a business that can bring profits and sustainability of business to have an impact on the increase in the economy of Islamic boarding schools in particular and society in general. The strategy starts from need assessment analysis, optimizing potential, supervision, and monitoring, and reflection, and evaluation.